Pengaruh Media Vidio Pembelajaran terhadap Hasil Pembelajaran Tematik pada Siswa Kelas VI SD Negeri Kejawat Kecamatan Brang Rea Kabupaten Sumbawa Barat - Faridah (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
This study aims to determine the effect of the use of video learning media on thematic learning outcomes in SD Negeri Kejawat, Brang Rea District, West Sumbawa Regency, 2019/2020 academic year. This research was conducted in 2 cycles with 1 meeting per cycle. The research subjects were teachers and students of grade VI SD Negeri Kejawat, Brang Rea District, West Sumbawa Regency, in the 2019/2020 academic year with a total of 5 students. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that using instructional video media could improve the thematic learning outcomes of Theme 2 (Unity in Differences) in Class VI SD Negeri Kejawat, Brang Rea District, West Sumbawa Regency, namely: (1) The skills of teachers through the use of video learning media increased. The increase in teacher skills was 18.73% from 72.93% in the first cycle with a good category to 91.66% in the second cycle with a very good category. (2) Student activity through the use of learning video media increased. The increase in student activity was 13.47% from 68.33% in the good category in the first cycle to 81.80% in the second cycle with a very good category. (3) Student learning outcomes through the application of learning video media have increased. Student completeness increased by 60% from 40% at the end of the cycle I to 100% at the end of cycle II. The data has reached the established success indicator of 80%.